Pengaruh Kepuasan kerja Terhadap Organizational Citizenship Behavior (OCB) Pada karyawan The Westin Resort & Spa Ubud Bali - Sanjaya, Farisa Nurfitri; Sulistyawati, Ni Luh Ketut Sri; Kalpikawati, Ida Ayu (Journal of Hospitality Accommodation Management (JHAM), 2024)
To increase competitiveness and achieve company goals, human resources must have additional behavior known as Organizational Citizenship Behavior. Various factors, such as employee satisfaction can influence the level of Organizational Citizenship Behavior in a company. This study aims to determine the effect of job satisfaction on Organizational Citizenship Behavior. The population uses employees who work at The Westin Resort & Spa Ubud, Bali as many as 120 employees using the saturated sample technique. The results of data analysis show that job satisfaction has a positive and significant effect on Organizational Citizenship Behavior, where the regression value is 0.607, The t-count value is 8.555> 1.981 and The significance value is 0.001 <0.05. The magnitude of the effect of job satisfaction on Organizational Citizenship Behavior is 38.3%. Researchers suggest that leaders of The Westin Resort & Spa Ubud, Bali improve employee cooperation through team building to strengThen interpersonal relationships and build trust, reward outstanding employees and conduct periodic evaluations.